Propriedades estruturais, magnéticas e dielétricas de ferritas do tipo Ni0,1Co0,4Zn0,5SmxNdyFe2-(x+y)O4 (x = y = 0,01; 0,02; 0,03; 0,04 e 0,05) para aplicação em dispositivos de micro-ondas - PEREIRA, Tayanne Cristina Marques Araújo (2019)
The aim of this research is to investigate the influence of rare earth (Sm3+ and Nd3+) additions on the structural, compositional, phonic, dielectric and magnetic properties of Ni-Zn-Co ferrite. Polycrystalline Ni0.1Co0.4Zn0.5SmxNdyFe2-(x+y)O4 (x=0.00; 0.01; 0.02; 0.03; 0.04 and 0.05) were prepared by the microwave-hydrothermal method. All samples were characterized using WDXRF, XRD, FTIR, Raman, VSM, Impedance spectroscopy and Coaxial probe techniques. The WDXRF analyses indicate no significant deviations between the theoretical and empirical stoichiometries of all the samples. The phase identification of the materials by XRD reveals the single-phase and cubic spinel structure of the samples. The estimated average crystallite sizes using Rietveld refinement were approximately 7.5 nm. The infrared and Raman spectra exhibit all the features of the cubic spinel structure reported in the literature. The insertion of rare-earth influenced the magnetic properties. An increase in coercive field and a decrease in saturation magnetization were observed. All the samples exhibit superparamagnetic characteristics, the magnetic average size for all the samples was very close to the estimated by Rietveld Refinement. The dielectric properties, such as dielectric constant (ε'), dielectric loss factor (ε"), dielectric loss tangent (tan δ) and AC conductivity have been undertaken over a wide range of frequencies. The measurement of ε' and ε" shows a decrease with the increasing frequency and tends to reach a constant value at higher frequency. The tan δ decreased with an increase in the frequency. AC conductivity increased with the rise of the frequency. The addition of the rare-earth modifies the dielectric characteristics in relation of the Ni-Zn-Co ferrite. The dielectric loss at high frequency presented low values for doped ferrites, making them good candidates for application in microwave devices.